The continental drift controversy - Frankel, Henry R., 1944- (Cambridge : Cambridge University Press, 2012)
'Resolution of the sixty year debate over continental drift, culminating in the triumph of plate tectonics, changed the very fabric of Earth Science. This three-volume treatise on the continental drift controversy is the first complete history of the origin, debate and gradual acceptance of this revolutionary theory. Based on extensive interviews, archival papers and original works, Frankel weaves together the lives and work of the scientists involved, producing an accessible narrative for scientists and non-scientists alike. This first volume covers the period in the early 1900s when Wegener first pointed out that the Earth's major landmasses could be fitted together like a jigsaw and went on to propose that the continents had once been joined together in a single landmass, which he named Pangaea. It describes the reception of Wegener's theory as it splintered into sub-controversies and geoscientists became divided between the'fixists' and'mobilists''--
vol. 1. Wegener and the early debate.
Includes bibliographical references and indexes.
Keywords: Continental drift -- Resarch -- History -- 20th century; Academic disputations -- History -- 20th century